Influence of Nitrogen Fertilization on Herbicide Selectivity in Rice - LANGARO,A.C. (2018)
ABSTRACT: Chemical weed control and nitrogen fertilization are common practices in irrigated rice crops. Nitrogen is an essential element for growth and development of plants and may influence herbicide selectivity. In this study, herbicide selectivity was evaluated according to nitrogen application time in irrigated rice crops. The experiment was conducted in the field in a split-plot design with four replications. Treatments were arranged in a factorial scheme: factor A consisted of different nitrogen application times (without nitrogen, all nitrogen applied before flooding, half of the nitrogen rate applied before flooding and the other half after flooding, all nitrogen applied after flooding); factor B consisted of the application of the herbicides quinclorac, bentazon, bispyribac-sodium and carfentrazone-ethyl. Nitrogen application increased plant height and dry matter accumulation in rice plants, while nitrogen application before flooding and split N applications were favorable to the crop. The herbicide bispyribac-sodium causes the greatest injury and the greatest reduction in rice plant height, followed by bentazon and carfentrazone-ethyl, while the lowest injury and the highest grain yield were caused by the application of quinclorac.